The rasterstereographic-dynamic analysis of posture in adolescents using a modified Matthiass test - Betsch, Marcel; Wild, Michael; Jungbluth, Pascal; Thelen, Simon; Hakimi, Mohssen; Windolf, Joachim; Horstmann, Thomas; Rapp, Walter (European Spine Journal, 2010)
The Matthiass posture test is a clinical test to detect posture changes in children and adolescents. Aim of this study was to objectify this test using a dynamic rasterstereographic measuring device. We examined 31 healthy athletes during a modified Matthiass test with a dynamic rasterstereographic measuring system. Hereby the trunk inclination, kyphosis and lordosis angle were measured. The trunk inclination decreased by about 50% of the basic value just by raising the arms. Additional weight loads of only 5% body weight (bw) resulted in significant changes of the posture (lordosis and kyphosis angle) during this test. With this rasterstereographic measuring device it seems to be possible to determine spinal posture changes under dynamic conditions. The results suggest that additional weights of 5% bw during the Matthias-test are enough to create significant deviations in posture parameters, even in healthy subjects. © 2010 Springer-Verlag.
CRIS-Team Scopus Importer:2022-07-20
Keywords: Dynamic examination; Matthiass test; Posture; Rasterstereography; Spine